NYC tornado terror - Fast, Cheryl-Lee; Takacs, Tibor; Cook, T.S. (Vancouver, Kanada : Fast (Tornado) productions, 2008)
Fear and tension fills the air of the Big Apple as deadly tornadoes and electrical storms lash the city. Being faced with by-the-book government scientists who insist in enforcing an inapplicable solution to the catastrophe, deputy mayor James Lawrence and his wife meteorologist Dr. Cassandra Lawrence are willing to go above and beyond their call of duty to try to keep New York City safe
Title from tile screen
Executive producer, Fernando Szew, Michael D. Jacobs
Cast: Nicole de Boer, Colby Johannson, Jerry Wasserman, Tegan Moss, Jennifer Copping
DVD Format
Keywords: Tornadoes -- Drama; Suspense in motion pictures